The Antigua and Barbuda Agenda for SIDS (ABAS) vision for the energy transition: A legal analysis - Francesco Sindico; Catherine Hall; Lennart Wegener; Emily Wilkinson (ODI, 2024)
This report reviews the negotiated text of the Antigua and Barbuda Agenda for SIDS (ABAS), focusing on sections that relate to climate change mitigation, to identify where priorities lie and to determine where (and what kind of ) support is being called for.
Keywords: 340